Moving on Up - Turnbull James, Kim; Vinnicombe, Susan; Harris, Hilary (International Executive Development Programs, 2018)
This article shows how a practical approach, developed at Cranfield School of Management, can shift the dials on the numbers of women executives in organizations. We illustrate how we have used our Inclusive Talent Management template to guide our partnership with HSBC’s 80,000-strong global Operations, Services and Technology division (HOST). The HOST Executive Committee (ExCo) established a programme called Accelerating for Difference to create a strong pipeline of female talent and achieve greater female representation, particularly at the most senior levels.